Predictors of erectile dysfunction in men living with HIV: A systematic review update - Mostafa Golshekan; Mahmood Abedinzade; Zahra Bostani Khalesi; Marzieh Shayesteh Fard (Elsevier, 2024)
Sexual problems, such as difficulty achieving or maintaining an erection, also known as ED, are common among men living with HIV. However, there is limited understanding of the factors associated with ED among this group. The purpose of this study was to conduct a systematic review of the predictors of ED among men living with HIV. We conducted thorough searches of internet search engines and various electronic research databases using specific keywords to March 2024. Original articles in Persian and English that examined the predictors of ED in HIV-infected men were eligible for inclusion. Two independent reviewers conducted data extraction and assessment. The study included thirty articles involving 65 to 5682 participants. The primary risk factors for ED included demographic characteristics (such as age, nicotine use, unemployment, and lower education level), psychological factors (fear of virus transmission, depression, anxiety, and a history of emotional, physical, or sexual abuse), treatment-related factors (long-term use of ART medication and delayed ART initiation), health-related factors (hepatitis B infection, current diabetes, dyslipidemia, atherosclerosis, substance abuse, poor sleep quality, and sleep apnea), and socioeconomic issues (stigma, negative HIV coping, and poverty). Higher levels of social support were associated with a lower risk of ED. This systematic review indicated that certain demographic characteristics, psychological, treatment-related, health-related factors, and socioeconomic issues among men living with HIV predict the likelihood of experiencing ED. Healthcare providers should consider incorporating routine ED assessments using validated tools as part of follow-up programs to improve the overall well-being of men living with HIV.